2017
DOI: 10.1038/ncomms14791
|View full text |Cite
|
Sign up to set email alerts
|

Light-sensing via hydrogen peroxide and a peroxiredoxin

Abstract: Yeast lacks dedicated photoreceptors; however, blue light still causes pronounced oscillations of the transcription factor Msn2 into and out of the nucleus. Here we show that this poorly understood phenomenon is initiated by a peroxisomal oxidase, which converts light into a hydrogen peroxide (H2O2) signal that is sensed by the peroxiredoxin Tsa1 and transduced to thioredoxin, to counteract PKA-dependent Msn2 phosphorylation. Upon H2O2, the nuclear retention of PKA catalytic subunits, which contributes to dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 70 publications
3
85
0
Order By: Relevance
“…Furthermore, photoperception could be related to photoreceptor-independent light-sensing mechanisms such as those described recently for Saccharomyces cerevisiae. Here, a peroxisomal oxidase generates H 2 O 2 in a light-dependent manner, and the H 2 O 2 is sensed by a peroxiredoxin to induce signaling (54). Whereas the addition of exogenous H 2 O 2 bypasses the requirement for the peroxisomal oxidase in yeast (54), it is not sufficient to induce conidiation in B. cinerea (J. Schumacher, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, photoperception could be related to photoreceptor-independent light-sensing mechanisms such as those described recently for Saccharomyces cerevisiae. Here, a peroxisomal oxidase generates H 2 O 2 in a light-dependent manner, and the H 2 O 2 is sensed by a peroxiredoxin to induce signaling (54). Whereas the addition of exogenous H 2 O 2 bypasses the requirement for the peroxisomal oxidase in yeast (54), it is not sufficient to induce conidiation in B. cinerea (J. Schumacher, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…ROS (H 2 O 2 ) production from cryptochrome, a blue light photoreceptor, occurs in Arabidopsis and Drosophila (Consentino et al ., ; Arthaut et al ., ). Other flavin‐containing enzymes could also generate O 2 ·− and then H 2 O 2 in the light, and it has been shown that a yeast mutant in peroxisomal acyl‐CoA oxidase is impaired in light‐induced H 2 O 2 production and downstream signalling (Bodvard et al ., ). As yeast lacks conventional photoreceptors, another flavin‐dependent protein must provide light–dark or circadian cues.…”
Section: Production Of H2o2: Enzymes and Subcellular Locationsmentioning
confidence: 97%
“…Given the contradictory nature of the evidence so far, it will be important to determine whether peroxisomes are always net sinks or whether they can also be sources. Interestingly, strong evidence for a specific signalling role for peroxisome‐sourced H 2 O 2 has been demonstrated in yeast (Bodvard et al ., ). Other features of peroxisome activity that will impinge on this question are the proliferation and increased mobility under oxidative stresses and the formation of peroxule extensions (Rodríguez‐Serrano et al ., ).…”
Section: Control Of H2o2 Concentration: How and Where?mentioning
confidence: 97%
“…H 2 O 2 can act as a second message and is then transduced by peroxiredoxin, which relays the signal to thioredoxin (Trx). Oxidized thioredoxins inhibit PKA-dependent phosphorylation, allowing Msn2 and Msn4 to concentrate in the nucleus (Bodvard et al, 2017). Kinases Rim15 and Yak1 can positively regulate Msn2/4 dependent transcription, for example of starvation-specific genes (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%